Reconfigurable notched wideband antenna using ebg structure - Majid, H. A. (John Wiley and Sons Inc., 2015)
In this article, a wideband monopole antenna with band notched reconfigurability is proposed. The antenna consists of a wideband monopole antenna, incorporated with reconfigurable electromagnetic bandgap (EBG) structures. Six EBG structures with different band notched frequency are used to achieve six band notched reconfigurations. The EBG structures are placed underneath the feed line of the antenna. A switch is placed at each EBG structure, and by controlling the state of the switch, the band notched operation of the EBG can be activated or deactivated. The proposed antenna is capable to provide useful features for the notched band UWB communication system.